2008
DOI: 10.1002/jor.20626
|View full text |Cite
|
Sign up to set email alerts
|

Variation of cyclic strain parameters regulates development of elastic modulus in fibroblast/substrate constructs

Abstract: Dynamic mechanical culture systems are a widely studied approach for improving the functional mechanical properties of tissue engineering constructs intended for loading-bearing orthopedic applications such as tendon/ligament reconstruction. The design of effective mechanical stimulation regimes requires a fundamental understanding of the effects of cyclic strain parameters on the resulting construct properties. Toward this end, these studies employed a modular cyclic strain bioreactor system and fibroblast-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 59 publications
3
42
0
Order By: Relevance
“…Tissue engineers are incorporating mechanical stimulation to enhance tendon tissue augmentations and replacements [134][135][136][137][138][139][140][141][142][143][144][145][146] . By mechanically preconditioning the tissue-engineered construct cell population prior to in vivo implantation, the cells may be better equipped to enhance the repair since they have been exposed to the appropriate mechanical environment 134,135 .…”
Section: Mechanical Loading In Tissue-engineering Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue engineers are incorporating mechanical stimulation to enhance tendon tissue augmentations and replacements [134][135][136][137][138][139][140][141][142][143][144][145][146] . By mechanically preconditioning the tissue-engineered construct cell population prior to in vivo implantation, the cells may be better equipped to enhance the repair since they have been exposed to the appropriate mechanical environment 134,135 .…”
Section: Mechanical Loading In Tissue-engineering Applicationsmentioning
confidence: 99%
“…Given the importance of physiological loading to maintain tendon homeostasis, investigators have shown that applying load promotes a tendon-like phenotype in both two and threedimensional culture conditions [139][140][141][142][143][144][145][146] . Ralphs et al showed that when tendon cells are cultured on a two-dimensional substrate and subjected to biaxial strain at 1 Hz for eight hours per day for a total of ninety-six hours, cells link together using actin adherens junctions along the principal line of strain to monitor tensile load 142 .…”
Section: Mechanical Loading In Tissue-engineering Applicationsmentioning
confidence: 99%
“…This has led tissue engineers to include mechanical stimulation in their construct formation protocols. [23][24][25][26][27][28][29][30][31][32][33] However, there is little data that elucidates how mechanical forces change the dynamics of fibroblast populations in cell culture systems. This is because most investigations are performed by examining the culture at fixed time points either during or after the mechanical stimulation protocol is complete.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the individual effects of different stimuli is difficult, since a cell is always subject to one influence in the presence of others. For instance, applied strain may modify elastic modulus of cell substrate (McCullen et al 2010b;Joshi and Webb 2008). For best comparison of results from studies in different laboratories, researchers should establish some standard induction schemes that can be logically adapted to suit individual needs (Kroeze et al 2011).…”
Section: Consideration Of Apparent Conflicts In Findingsmentioning
confidence: 99%
“…Additionally, nanoscale topographical features in growth substrates influence stem cell behavior (Teo et al 2010). Finally, elasticity has a plausible effect on osteogenesis of ASC (Hanson et al 2009;Engler et al 2006;McCullen et al 2010b;Joshi and Webb 2008).…”
Section: Hypotheses Of Mechanismmentioning
confidence: 99%